Penguatan Kompetensi Guru Melalui Manajemen Sdm Pendidikan: Analisis Konseptual Dan Strategi Implementasi - Hafiedz, Kholid Abdul; Ali, Moh; Cahyani, Dewi (Universitas Pakuan, 2025)
STRENGTHENING TEACHER COMPETENCE THROUGH EDUCATIONAL HUMAN RESOURCES MANAGEMENT: CONCEPTUAL ANALYSIS AND IMPLEMENTATION STRATEGYImproving teacher competence is a key factor in enhancing the overall quality of education. This article aims to analyze the integration of educational administration and human resource management (HRM) as a comprehensive approach to strengthening teacher competence. Using a literature review method, this study examines concepts, principles, and empirical findings related to the role of educational administration in policy formulation, program planning, supervision, and evaluation of teacher development, alongside HRM functions such as human resource planning, recruitment, selection, training, performance appraisal, and work motivation. The findings indicate that integrating these two disciplines creates a more effective and sustainable framework for teachers’ professional development. Educational administration provides structural and strategic direction, while HRM ensures that teachers are managed as human capital through systematic development processes. Implementation challenges identified include budget limitations, managerial capacity gaps, weak collaborative culture, and suboptimal use of data for decision-making. This article concludes that the synergy between educational administration and HRM is a relevant and strategic approach to strengthening teacher competence in schools.